Removal of bulk CO2 from methane with the presenceof heavy hydrocarbon using polyimide membrane - Jusoh, N. (Penerbit UTM Press, 2014)
The membrane process has advanced rapidly and continued to progress due to its advantages. Polyimide membrane has been widely applied for gas separation due to their promising permeability and selectivity. In this paper, the effect of heavy hydrocarbon (pentane) in removing bulk CO2 from methane using polyimide membrane was studied. Higher operating pressure and temperature demonstrated the increment of CO2 and CH4 permeance while CO2/CH4 selectivity decreased for both dry and wet conditions. As CO2 concentration increased, CO2 and CH4 permeance as well as CO2/CH4 selectivity enhanced. The presence of pentane in membrane separation contributed to the loss of CO2/CH4 selectivity. Â© 2014 Penerbit UTM Press. All rights reserved.